Unraveling the magnetic properties governing domain-wall dynamics in ferromagnets: a peculiar reversal phenomenon - 김민환; Choe, Sug-Bong; Kim, Duck Ho (2023 KPS Spring Meeting, 2023)
The dynamic behavior of elastic interfaces in ferromagnets under driving forces has been extensively studied forfundamental understanding of physics and as a promising candidate for next-generation spin memory and logic devices [1, 2]. There are two distinct dynamic regimes for domain walls (DWs): thermally activated DW creep motion and dissipative viscous DW flow motion [3]. Despite remarkable efforts to understand how DW motion depends on external driving forces, the role of magnetic properties on DW motion forthe different dynamic regimes remains elusive. In this study, we experimentally observed that the dynamics of magnetic DWs are governed by distinct key factors for different dynamic regimes, resulting in a peculiar phenomenon of reversal in the speed of DWs with respect to ferromagnetic thickness between the two dynamic regimes. Ourfindings provide a better understanding of how magnetic properties and volume influence DW dynamics and offer a simple rule for controlling DW motion. Details will be discussed in the presentation.